The epidemiological features and pathogen spectrum of respiratory tract infections, Istanbul, Türkiye, from 2021 to 2023 - Karabulut, Nuran; Alaçam, Sema; Şen, Esranur; Karabey, Mehmet; Yakut, Nurhayat (My University, 2024)
Respiratory tract infections (RTIs) can lead to both recurrent seasonal epidemic outbreaks and devastating pandemics. The aim of this study was to evaluate the epidemiologic characteristics and pathogen spectrum of RTIs using a multiplex RT-PCR panel. A total of 9354 cases with suspected RTIs between February 2021 and July 2023 were included in this study. A total of 11,048 nasopharyngeal and oropharyngeal samples from these patients were analyzed for 23 respiratory tract pathogens using multiplex RT-PCR. H. influenzae and S. pneumoniae were considered as colonizing bacteria. At least one pathogen was detected in 70.66% of the samples; viral pathogens were detected in 48.41% of the samples, bacterial pathogens were detected in 16.06% of the samples, and viral + bacterial pathogens were detected in 35.53% of the samples. The most frequently detected viral pathogen was rhinovirus/enterovirus (RV/EV) (19.99%). Interestingly, in 2021, respiratory syncytial virus A/B showed atypical activity and replaced RV/EV as the most prevalent pathogen. Human bocavirus, H. influenzae, and S. pneumoniae were detected at higher rates in males (p: 0.038, p: 0.042, and p: 0.035, respectively), while SARS-CoV-2 and B. pertussis were detected at higher rates in females (p < 0.001 and p: 0.033). RTIs were found at higher rates in children (p < 0.001). SARS-CoV-2 and human coronaviruses 229E were detected at higher rates in adults (p < 0.001 and p: 0.001). This comprehensive study with a large sample size investigating RTI pathogens was the first in Türkiye. Understanding the current viral circulation using multiplex RT-PCR panels enables clinicians to predict the most likely pathogens affecting patients and contributes to patient management, in addition to anticipating potential threats.
Keywords: Influenzae Viruses; Multiplex RT-PCR; RSV; SARS-CoV-2